Water, Human Rights and Legal Pluralism - Von Benda-Beckmann, Franz; Von Benda-Beckmann, Keebet (Water Nepal, 2003)
The human rights catalogue is becoming increasingly important not only for rights to land but also to water. Non governmental organisations and others increasingly discuss the right to water in terms of human rights. Such a development has obvious advantages, but it may also be problematic. This paper lays out some of the problems that might emerge and that will need to be addressed. Recent studies on rights to irrigation water in Nepal indicate that the legal situation can be characterised as pluralistic. State regulation at different levels has created normative and institutional framework that is often at odds with the traditional normative and institutional framework related to water. In addition, international organisations, e.g. those which aim to improve irrigation systems, tend to add their own set of norms and decision making processes that sometimes do not tie in either with the legal structure of the state or with customary law. The new trend towards discussing rights to water in terms of human rights may also turn out to be a new source of complexity. Referring to examples from Indonesia related to land, this paper identifies some problematic aspects of such increased complexity.Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.63-76